Single nucleotide polymorphism at cluster of differentiation 14 (CD14) gene and its association with fertility traits in crossbred cattle of Kerala - Sadan, Tina; Valsalan, Jamuna; Venketachalapathy, Thirupathy; Anilkumar, K.; Aravindakshan, T V (Indian Journal of Dairy Science, 2020)
Cluster of differentiation 14 (CD14) gene is an important molecule for innate unity and found to be significantly associated with fertility traits in cattle. The objectives of present study were to detect the single nucleotide polymorphisms (SNPs) in exon 1 region of CD14 gene and to evaluate the association of genetic variants with fertility traits viz. Service period and Age at First Calving in crossbred cattle of Kerala. The study was conducted on two hundred and sixteen crossbred cattle maintained at various farms of Kerala Veterinary and Animal Sciences University. Genomic DNA was isolated and polymorphisms of gene were detected by Single Strand Confirmation Polymorphism. Two SNPs, c.445T>G and c.432C>T were detected in exon 1 coding region of CD14 gene. The frequencies of CC and CT genotypes were 0.82 and 0.18 in the population. In addition, a significant association between SNPs and service period was observed in crossbred cattle population under study. Crossbred cattle with CT diplo types showed lower values for service period than those with CC diplo types. The association of CD14 gene with these traits emphasizes the importance of bovine CD14 as a candidate gene for marker assisted selection for fertility traits in crossbred cattle